2017
DOI: 10.1002/cptc.201700123
|View full text |Cite
|
Sign up to set email alerts
|

Naphthalimide‐Containing Isomeric Urea Derivatives: Mechanoluminescence and Fluoride Recognition

Abstract: Isomeric ortho, meta and para naphthalimide–urea derivatives ND‐2U, ND‐3U and ND‐4U were synthesized and characterized. Upon gentle mechanical stimulation, the weakly emissive ortho isomeric sample ND‐2U was transformed into a yellow‐green emissive material (λem=500 nm), with Δλ≈125 nm. The mechanoluminescent emission of this isomer could be “switched off” by exposing the sample to solvent vapour. Moreover, ND‐2U could respond to fluoride anions in solution with a dramatic enhancement of fluorescence at λ=446 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…Despite the extensive and growing literature on fluoride recognition chemistry, very few synthetic hydrogen bonding receptors have been shown to capture or recognize fluoride in an aqueous environment. ,, In short, it is very challenging to design a hydrogen bonding system that can compete with the very high enthalpy of fluoride hydration (504 kJ mol –1 ). , This point is highlighted by the scarcity of synthetic hydrogen bonding receptors that can extract fluoride from water. ,,, But the need for fluoride extractors is very high since fluoride is a known pollutant that must be monitored and removed from various types of aqueous reservoirs such as polluted lakes . A very different motivation to develop supramolecular receptors for fluoride is to improve the efficiency and lifetime of fluoride-containing electrolytes within redox devices such as fluoride-ion batteries which have high potential as next-generation electrochemical storage devices .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the extensive and growing literature on fluoride recognition chemistry, very few synthetic hydrogen bonding receptors have been shown to capture or recognize fluoride in an aqueous environment. ,, In short, it is very challenging to design a hydrogen bonding system that can compete with the very high enthalpy of fluoride hydration (504 kJ mol –1 ). , This point is highlighted by the scarcity of synthetic hydrogen bonding receptors that can extract fluoride from water. ,,, But the need for fluoride extractors is very high since fluoride is a known pollutant that must be monitored and removed from various types of aqueous reservoirs such as polluted lakes . A very different motivation to develop supramolecular receptors for fluoride is to improve the efficiency and lifetime of fluoride-containing electrolytes within redox devices such as fluoride-ion batteries which have high potential as next-generation electrochemical storage devices .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also demonstrated how intermolecular interactions and molecular packing of organic molecules can be influenced by mechanical stimuli (i.e., pressure, stress). , This understanding has paved the way for the design of mechano-responsive organic materials, wherein the packing behavior, and hence the luminescence properties can be controlled and tuned by using mechanical stimuli. , …”
Section: Introductionmentioning
confidence: 99%
“…Among the numerous mechano-responsive π-conjugated organic fluorophores reported to date, ,, the anthracene motif has been recognized as a versatile building block. ,,,, However, a major impediment with the anthracene motif is its tendency to form face-to-face aggregates, assisted by favorable π-stacking interactions. Such interactions predominate in the solid or condensed states and result in bathochromic shifting of fluorescence or quenching of the excited states through nonradiative pathways. , Nonetheless, several anthracene derivatives have been reported that show stimuli-responsive luminescent emissions. ,, …”
Section: Introductionmentioning
confidence: 99%
“…In comparison, the major diffraction peaks of the yellow emissive A-4OH-Y form were shifted to lower 2 θ values, 2 θ = 6.58°, 8.78°, 13.24° and 19.84°, indicating an increase in the d -spacing of the crystal lattice. 48,49 As evident from the above results, thermally induced desolvation of A-4OH-NE crystals triggered the reorganization of the anthracene planes possibly due to the loss of DMF molecules from the lattice.…”
Section: Resultsmentioning
confidence: 73%